Hubungan Kondisi Sanitasi Rumah dan Praktik Saniter dengan Kejadian Diare - Hidayah, Nurul; Wijayanti, Yuni (Jurnal Penelitian dan Pengembangan Kesehatan Masyarakat Indonesia, 2023)
Background: Poor sanitation and floods can increase the potential for diarrhea. The incidence of diarrhea in Semarang City has increased by 10,723 cases in 2022, to 32,488 cases. The purpose of this study was to determine the relationship between house sanitation conditions and sanitary practices with the incidence of diarrhea in flood-prone settlements. Method: this type of research is descriptive analytic using a cross sectional approach with simple random sampling technique at 92 houses/respondents. The instruments used were observation sheets and questionnaires. Data analysis used chi square test. Results: There is a relationship between the sanitation conditions of the walls of the house (p=0.006), wastewater sewerage (p=0.014), and solid waste disposal (p=0.001), as well as household waste protection (p=0.001) and washing hand with soap (p=0.014) with the incidence of diarrhea, while the sanitary condition of the floor of the house (p=0.122) not related to the occurrence of diarrhea.